(untitled) (Research, Society and Development, 2021)
Historically, the Physical Education curricular component was far from the policies associated with the production of didactic material, especially with regard to the textbook (LD). The absence of this material is the reason for many conflicts regarding its importance,one as an instrument that directs and guides the teacher in the teaching-learning process, theother as an instrument that crystallizes the teaching activity. Therefore, this work meets this material, previously unpublished in the field of School Physical Education. Having as central objective to analyze the textbooks of Physical Education for beginning series of the basic education in the light of the Common Curriculum Nacional Base. Therefore, it has a qualitative character of a descriptive nature under a documentary bias. Data analysis used the content analysis technique. The results showed that the collection “bodily practices” has similarities with the Common Base National Curriculum, however, at times, this approximation is not made in a clear and objective way, especially when we think about its use by a multipurpose teacher. However, in its activities, proposed at the end of each new content, it inserts, in its majority, the students in a diversified field of knowledge, mainly with regard to their geographic reality. Therefore, it is important to highlight that the textbook, in addition to the written pages, needs complements, related to planning, to the teacher’s experiences, to the skills developed and under development by the class.